Upaya Meningkatkan Hasil Belajar Matematika dengan Pendekatan Contextual Teaching and Learning (CTL) pada Siswa Kelas V Semester I Tahun Pelajaran 2019– 2020 di SDN 2 Setanggor - Wirya, Baiq Sri Olati (Lembaga Yasin AlSys, 2021)
This study aims to improve student's learning outcomes in solving mixed calculation problems with contextual teaching and learning (CTL) approaches. This research method is a type of classroom action research. This class action research was conducted at SD Negeri 2 Setanggor which is addressed to Lendek Village, Sukamulia sub-district. The implementation of this study was carried out in class V of the 2019/2020 school year with a total of 27 students. Based on the discussion of the results of the cycle I and cycle II research it can be concluded that using car-car props on the calculation of integer calculation operating materials with contextual teaching and learning (CTL) approach, can improve student learning outcomes this is proven: In cycle, I the number of students completed on the main operation calculates integers (addition and subtraction) with contextual teaching and learning (CTL) approach is 66% or 18 of the 27 students. In cycle II, the percentage of student completion experienced improvements with the contextual Teaching and Learning (CTL) approach which is as much as 85% or 23 out of 27 students.